2011
DOI: 10.1007/s00382-011-1177-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atmosphere-ocean general circulation model simulations of winter northern hemisphere atmospheric blocking

Abstract: An assessment of six coupled AtmosphereOcean General Circulation Models (AOGCMs) is undertaken in order to evaluate their ability in simulating winter atmospheric blocking highs in the northern hemisphere. The poor representation of atmospheric blocking in climate models is a long-standing problem (e.g. D'Andrea et al. in Clim Dyn 4:385-407, 1998), and despite considerable effort in model development, there is only a moderate improvement in blocking simulation. A modified version of the Tibaldi and Molteni (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
(59 reference statements)
2
45
0
Order By: Relevance
“…Hence, blocking research mainly relies on model output and reanalysis data rather than using direct observations. However, most models show only limited skill in blocking representation, as has been noted by many studies in the past (D'Andrea et al, 1998;Vial and Osborn, 2012;Barnes et al, 2012;Anstey et al, 2013;Christensen et al, 2013;Dunn-Sigouin and Son, 2013;Masato et al, 2013). Recently, Davini and D'Andrea (2016) showed that current climate models still underrepresent blocking occurrence by up to 50 %, particularly in the Euro-Atlantic blocking region.…”
Section: Introductionmentioning
confidence: 95%
“…Hence, blocking research mainly relies on model output and reanalysis data rather than using direct observations. However, most models show only limited skill in blocking representation, as has been noted by many studies in the past (D'Andrea et al, 1998;Vial and Osborn, 2012;Barnes et al, 2012;Anstey et al, 2013;Christensen et al, 2013;Dunn-Sigouin and Son, 2013;Masato et al, 2013). Recently, Davini and D'Andrea (2016) showed that current climate models still underrepresent blocking occurrence by up to 50 %, particularly in the Euro-Atlantic blocking region.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, much of the warming that occurred in the late 20th century in Europe has been attributed to the increased number of winters with a high-index AO/NAO (Hurrell, 1995;Visbeck et al, 2001). High-index AO/NAO conditions are also thought to have occurred during the Medieval Climate Anomaly, providing a dynamic explanation for the winter warmth experienced over Europe at this time .…”
Section: The Atmospheric Circulationmentioning
confidence: 99%
“…One of the main sources of uncertainty in determining regional climate change in the mid-latitude regions such as Europe is the atmospheric circulation, a feature of the climate system that models have difficulty to simulate (Gillett, 2005;van Ulden and van Oldenborgh, 2006;Woollings, 2010;Vial and Osborn, 2012;Brands et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing Northern Hemisphere (NH) blocking characteristics across a range of models from phase 3 of the Coupled Model Intercomparison Project (CMIP3), Vial and Osborn (2012) found the frequency of blocking episodes to be underestimated owing to an excessive number of shortlived blocking events at the expense of prolonged blocking episodes. Such deficiencies have often been attributed to insufficient horizontal resolution, where small-scale features, such as atmospheric eddies important for maintaining larger-scale blocking patterns through positive feedbacks, are insufficiently resolved (Kug and Jin 2009;Scaife et al 2011, and references therein).…”
Section: Introductionmentioning
confidence: 99%